Subnational public expenditures, short-term household-level welfare, and economic resilience: Evidence from Nigeria - Takeshima, Hiroyuki; Balana, Bedru; Smart, Jenny; Edeh, Hyacinth O.; Oyeyemi, Motunrayo Ayowumi; Andam, Kwaw S. (International Food Policy Research Institute, 2021)
Public expenditures (PE) are critical for key public sector functions that contribute to development and welfare improvements, including the provisions of necessary public goods and the mitigation of market failures. PE in social sectors, such as health, education, and social welfare, and in agriculture have been increasingly recognized as potentially important for income growth, poverty reduction, fostering increased private investment, improved nutritional outcomes, and greater economic resilience. Furthermore, the importance of the impact of subnational PE on these outcomes has also been recognized, as appropriately decentralized PE systems can potentially achieve greater effectiveness by enabling public sector support that is tailored more to local needs. However, direct evidence of these developmental effects of decentralized PE in developing countries like Nigeria has been relatively limited. This study attempts to fill this knowledge gap by estimating the effects of shares of total subnational PE for agriculture, health, education, and social welfare, as well as PE size, on household-level outcomes using nationally-representative panel household data and both local government area and higher state-level PE data for Nigeria. We find that greater shares of total PE for agriculture, health, and social welfare, conditional on PE size, generally have positive effects on consumption, poverty reduction, and non-farm business capital investments. A greater share of total PE for agriculture benefits a broader range of outcomes than do greater shares of total PE for health and social welfare. These include improving certain nutritional outcomes, like household dietary diversity across seasons, and economic flexibility between farm and non-farm activities, which may be particularly important for building resilience in today’s rapidly changing socioeconomic environment due to shocks, including COVID19. Such multi-dimensional benefits of greater PE for agriculture are particularly worthy of attention in countries like Nigeria, which have historically allocated a lower share of total PE to agriculture than to health and other social welfare sectors and a lower share of total PE to agriculture compared to that allocated to agriculture in similar countries in Africa and elsewhere.